Konflik Identitas dan Budaya Antar Suku di Yogyakarta, Heterogenisasi Vs Homogenisasi : (Dinamika Peran Keraton dan Filosofi Keistemewaan Yogyakarta dalam Menangani Konflik) - Muhammad Rouf Mustofa; Ita Rodiah (Universitas Merdeka Madiun, 2024)
Student groups or communities living in Yogyakarta create fuses that can catch fire at any time. Groups in Yogyakarta have the potential to experience offense caused by various aspects. The frequent occurrence of identity and ethnic conflicts is quite disturbing, especially for indigenous people. Yogyakarta society is facing the challenge of homogeneity in particular, long before theories and studies about the dangers of homogeneity, there were several special philosophies that the Yogyakarta people always adhered to in carrying out their life roles. The role of the Palace and the implementation of the special philosophy in Yogyakarta has not been fully understood by most people, especially immigrants. The collaboration between the religious patterns of Yogyakarta society and the philosophy of privilege is very closely related to the concept of Islam Nusantara. Indirectly, it is hoped that such collaboration with the heterogeneous society of Yogyakarta can reduce homogenization conflicts, both religious and cultural. One of them is the